STRUCTURE, AC CONDUCTIVITY AND POWER LOSSIN PVC AND PMMA POLYMERS - Ahmed, Hameed; Aziz, Shuja-Aldeen (Iraqi Journal of Science, 2024)
Frequency and temperature dependence of AC-conductivity (AC) and power loss (W) for polyvinyl chloride (PVC) and poly (methyl methacrylate) (PMMA) were studied (in the frequency range 1KHz-1MHz and in the temperature range 20-100°C). It has been found that the AC-conductivity increases with increasing frequency and temperature for both samples. The value of the exponent is less than 1 for both samples as determined experimentally. The power loss which is in the form of heat, is increased for both samples with increasing frequency and temperature. The IR spectra shows the presence of C-Cl and C=O bond, which are the main sources for power loss.